THE CONTRIBUTION OF TECHNOLOGY TO AN UNDERGRADUATE INTERNATIONAL LEARNING PARTNERSHIP: THE RITUAL PERSPECTIVE - Ločmele, Liene; Burke, Barbara Ruth (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This study is part of a research project on a learning partnership between undergraduates of ViA, Latvia and UMM, USA. During the joint media course in Spring 2016, students participated in Skype discussions, completed shared assignments and reflected upon their learning experience. The transcripts of these activities form the body of qualitative data. We employ the perspective of Ethnography of Communication (Hymes 1962, Philipsen 1997) and Cultural Discourse Analysis (Carbaugh, 2007) in order to answer the following research questions: (1) what is the nature of the studied technology-mediated learning discourse, and (2) how do the constructed meanings around the use of technology contribute to the variety of cultural norms in play? We propose to understand the studied discussion sessions as a ritual practice (Turner 1980, Philipsen 1992, 1997)–the correct performance of which the participants instantly co-construct and negotiate when employing locally-adopted norms associated with democratic education practice–and assess the use and function of technology in the experienced learning interactions.